2011
DOI: 10.1007/s00335-011-9385-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping of loci for antipsychotic-induced extrapyramidal symptoms in mice

Abstract: Tardive dyskinesia (TD) is a debilitating, unpredictable and often irreversible side effect resulting from chronic treatment with typical antipsychotic agents such as haloperidol. TD is characterized by repetitive, involuntary, purposeless movements primarily of the orofacial region. In order to investigate genetic susceptibility to TD, we used a validated mouse model for a systems genetics analysis geared toward detecting genetic predictors of TD in human patients. Phenotypic data from 27 inbred strains chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…Previous work (Crowley et al, 2012a; Crowley et al, 2012b) indicated that 3.0 mg/kg/day haloperidol delivered via continuous 60-day slow release subcutaneous pellets (Innovative Research of America, Sarasota, FL) yielded plasma haloperidol concentrations in mice in the 10– 50 nM range with lower variation as compared to minipumps, repeated injections or oral administration. Furthermore, this dose and delivery method has been previously demonstrated to produce vacuous chewing movements in C57BL/6J mice that peaked around four weeks and persisted for over one year, long after drug administration ended (Crowley et al, 2012a).…”
Section: Methodsmentioning
confidence: 99%
“…Previous work (Crowley et al, 2012a; Crowley et al, 2012b) indicated that 3.0 mg/kg/day haloperidol delivered via continuous 60-day slow release subcutaneous pellets (Innovative Research of America, Sarasota, FL) yielded plasma haloperidol concentrations in mice in the 10– 50 nM range with lower variation as compared to minipumps, repeated injections or oral administration. Furthermore, this dose and delivery method has been previously demonstrated to produce vacuous chewing movements in C57BL/6J mice that peaked around four weeks and persisted for over one year, long after drug administration ended (Crowley et al, 2012a).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study (Crowley et al 2012b), only 3 of 27 inbred strains manifested a substantial amount of toxicity after haloperidol treatment, and the latency in A/J mice was substantially larger (36% and 59%) than that of the other two strains (NZW and NZO). Therefore, it was possible that A/J mice uniquely had an additional pharmacogenetic factor that increased its susceptibility to HIT.…”
Section: A Novel Pharmacogenetic Factor For Hitmentioning
confidence: 71%
“…We recently analyzed a murine genetic model of haloperidol-induced toxicity (HIT) (Zheng et al 2015) in which the Parkinsonian-like symptoms developing in haloperidol-treated mice resemble those observed in drug-treated human patients (Crowley et al 2012a). The 27 inbred strains evaluated in this genetic model exhibit substantial variability in susceptibility to HIT (Crowley et al 2012b). For example, C57BL/6 mice are completely resistant, while A/J mice are highly susceptible to the Parkinsonian hypokinesia associated with HIT.…”
mentioning
confidence: 99%
“…Since the early 1970s, rats that were exposed to dopamine receptor blocking agents for consecutive weeks manifested different patterns of purposeless, chewing activity, which is termed “vacuous chewing movements”(2225, 3034). VCM are also observed in mouse models of TDS (55, 56). The VCM induced by haloperidol was further exacerbated by knocking out Nur77 (57).…”
Section: Pathophysiology Of Tdsmentioning
confidence: 91%